Spatial diffusion patterns of call-centers in the Netherlands - Frank Bruinsma; Piet Rietveld; Michiel Beekman (European Regional Science Association (ERSA), 2002)
The focus in this paper is on spatial diffusion patterns of call centers in The Netherlands. The number of call centers has increased rapidly in the last decade and it seems that impacts of call centers on the labor market still underestimated. We will pay attention to two spatial levels: first urban versus rural and second local. Given the labor intensity and quality required by call centers and the absence of physical contacts with consumers one might expect that most call centers are located in the more peripheral parts of the country. In those peripheral areas there is less pressure on the labor market and the level of education - in particular the ability to speak English - is almost as good as elsewhere in the country. At the local level we are interested in the precise location of the call centers. We expect that they will prefer back office locations or even locations on cheap industrial sites, again due to the absence of physical contacts with consumers. They only will need enough parking space for their employees, since this is a relatively labor intensive economic activity. In this inventory study we will analyze the spatial diffusion patterns of call centers in The Netherlands and link them to regional labor market developments and other location factors.
Keywords: 330